MEMBANGUN MODAL SOSIAL DALAM KONTRA TERORISME - Hidayat, Safril (Jurnal Pertahanan dan Bela Negara, 2016)
Social capital is a quality that can be a facilitator of interpersonal cooperation. Social capital is about the value of social networks, bonding similar people and bridging between diverse people, with norms of reciprocity. Social capital can aggregate bonds, bridges, and linkages between apparatus and citizens. However understanding terrorism should be the firts task. To understand terrorism, therefore the same definition should be shaped as national or common perception of terrorism. Studies have found more than 200 definitions of terrorism. If the definition of terrorism widely agreed and acceptable, thus the counterterrorim can be taken with realistic and fair indicators of success, and accountable. It is weird but real that common people generalized terrorism as Islamist, thus terrorism is pointed to moslem followers. As a basic or fundamental to define terrorism, all people should understand value and norms which all moslem adopted and followed. From this point, the common understanding will build common interest that all people aware of terrorism and has willing altogether to take counter terrorism actions. Therefore, the higher social capital will reach the higher governmental efforts to counter terrorism. Â  Keywords: Social Capital, Terrorism, Counterterrorism, Islam Norms, Islam Values.